Chopin - Grottger - Poniatowska, Irena (Interdisciplinary Studies in Musicology, 2018)
Is Stanisław Tarnowski’s linking of Fryderyk Chopin and Artur Grottger in his Dwa szkice [Two sketches] justified? Well, the connection is substantiated by the “Romantic-leaning” point of view and the idea of the correspondance des arts that characterised the nineteenth century in which the two creative artists (and Tarnowski himself) lived, although they represented different creative fields. Both the musician Chopin and the artist Grottger were regarded as poets. The former on account of the poetic of his piano playing and musical works, the latter for the poetical dimension of his pictures devoted to the January Rising. Tarnowski called Chopin the fourth bard of Poland, alongside Adam Mickiewicz, Juliusz Słowacki and Zygmunt Krasiński, and Grottger the poet of the Rising, since - as he paradoxically stated - the poetical narrator of those events could only be an artist. Terminology of a literary character belonged to the lexicon of notions employed by critics of art and music at that time. Besides this, the national character is inscribed in the idiom of the work of both these creative artists - the thoroughly patriotic stance that was so strongly manifest in the output of Polish romanticism. Another common denominator in their work is the concept of the cycle. With Chopin, the 24 Preludes, Op. 28 comprise a cycle in which the bonding element is the succession of major keys and their relative minor keys according to the circle of fifths, but they are also an expressive cycle of various states of mind, from despair to joyous reverie. The Preludes show both the semantic capacities and the suppleness of Chopin’s musical language; that is, the ability to express the same feelings through various purely musical means, without any programmatic motto. With Grottger, we have the cycles Warszawa [Warsaw] (two cycles), Polonia, Lituania and Wojna [War]. In them, the metonymy of the narrative sequences is coupled with the notional exposition, with the symbolism. Grottger portrays not the historical scenes of the Rising, but the feelings of grief, despair and fear of individual people, reflecting their experiences. And so the concept is similar. Chopin’s Preludes are like sketches, aphoristic utterances; sketches are also important in the work of Grottger, partly as a self-contained genre. A third plane of analogy is the reduction of media. Chopin confines himself essentially to the piano, from which he produces startling tonal qualities, although he did write several works for chamber or orchestral forces. Grottger, meanwhile, draws his cycles solely in black pencil, using white only to heighten contrasts and give the effect of chiaroscuro. He did not wish to distract the attention of viewers, but wanted them to concentrate on the symbol.